Increased of Knowledge, Attitudes, and Nutrient Intake Pregnant Women Through a Thousand Days First Life Media Drama - Mardiana, Mardiana; Yulianto, Yulianto; Yuniarti, Hana; Susanto, Eddy (Universitas Islam Lamongan, 2020)
Nutrition counseling is a learning process to develop understanding and positive attitudes towards nutrition so as to form and have good eating habits. The research aims to increase knowledge and attitudes as well as nutrition intake of pregnant women through the media drama of the first thousand days of life at the 11 Ilir Health Center in Palembang. Types of research Quasi-experimental with pretest posttest with control design. The results of the independent t test statistic test found a significant effect of 1000 HPK Drama Interventions on the average score of knowledge, attitude, intake of E, P, KH, Fe, and there was no effect of fat intake of respondents in both groups